Differences in medication adherence by sex and organ type among adolescent and young adult solid organ transplant recipients. (7th December 2022) - Vaisbourd, Yulia; Dahhou, Mourad; Zhang, Xun; Sapir‐Pichhadze, Ruth; Cardinal, Heloise; Johnston, Olwyn; Blydt‐Hansen, Tom D.; Tibbles, Lee Anne; Hamiwka, Lorraine; Urschel, Simon; Birk, Patricia; Bissonnette, Janice; et al.
Abstract: Background: Identification of differences in medication adherence by sex or organ type may help in planning interventions to optimize outcomes. We compared immunosuppressive medication adherence between males and females, and between kidney, liver and heart transplant recipients. Methods: This multicenter study of prevalent kidney, liver and heart transplant recipients 14–25 years assessed adherence 3 times (0, 3, 6 months post‐enrollment) with the BAASIS self‐report tool. At each visit, participants were classified as adherent if they missed no doses in the prior 4 weeks and non‐adherent otherwise. Adherence was also assessed using the coefficient of variation (CV) of tacrolimus trough levels; CV < 30% was classified as adherent. We used multivariable mixed effects logistic regression models adjusted for potential confounders to compare adherence by sex and by organ. Results: Across all visits, males ( n = 150, median age 20.4 years, IQR 17.2–23.3) had lower odds of self‐reported adherence than females ( n = 120, median age 19.8 years, IQR 17.1–22.7) (OR 0.41, 95% CI 0.21–0.80) but higher odds of adherence by tacrolimus CV (OR 2.50, 95% CI 1.30–4.82). No significant differences in adherence (by self‐report or tacrolimus CV) were noted between the 184 kidney, 58 liver, and 28 heart recipients. Conclusion: Females show better self‐reported adherence than males but greater variability in tacrolimus levels. Social desirability bias, more common in females than males, may contribute to better self‐reported adherence among females. Higher tacrolimus variability among females may reflect biologic differences in tacrolimus metabolism between males and females rather than sex differences in adherence. There were no significant differences in adherence by organ type.